1996
DOI: 10.1002/pen.10518
|View full text |Cite
|
Sign up to set email alerts
|

On the use of PET‐LCP copolymers as compatibilizers for PET/LCP blends

Abstract: Copolyesters of poly[ethylene terephthalate) (PET) with a liquid crystalline polymer (LCP), SBH 1:1:2, have been synthesized by the polycondensation, carried out in the melt at temperatures up to 300 degrees C of sebacic acid (S), 4,4'-dihydroxybiphenyl (B), and 4-hydroxybenzoic acid (H) in the presence of PET. The PET-SBH copolyesters have been characterized by differential scanning calorimetry, scanning electron microscopy, X-ray diffraction, etc., and the relationships between properties and preparation con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

1998
1998
2001
2001

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 37 publications
(7 reference statements)
1
11
0
Order By: Relevance
“…Thus, the droplets were in the LC state at the end of the synthesis, and appear as monodomains when the cryofractured material is viewed with the electron microscope (Rg. 6). Because the two phases of COP-2 have closer chemical composition and, hence, fairly good interfacial adhesion, the U P droplets are severely involved in the fracture thus allowing a direct observation of the structure of the nematic domains.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the droplets were in the LC state at the end of the synthesis, and appear as monodomains when the cryofractured material is viewed with the electron microscope (Rg. 6). Because the two phases of COP-2 have closer chemical composition and, hence, fairly good interfacial adhesion, the U P droplets are severely involved in the fracture thus allowing a direct observation of the structure of the nematic domains.…”
Section: Resultsmentioning
confidence: 99%
“…This approach proved unsuccessful, however, when we tried to synthesize p(ETHSB) copolyesters by the transesterification of p(ET) with a mixture of H, sebacic acid (S), and 4,49-diacetoxybiphenyl (B). [24] In fact, the presence of S did increase considerably the tendency of the reaction mixture to separate into an aromatic-rich nematic phase and an isotropic phase rich of E and S units, with the result that a true "synthetic blend" composed of a low melting isotropic matrix with high melting LCP inclusions was finally obtained. [24] On the contrary, Li et al, [25,26] who investigated the synthesis of p(ETHX) copolyesters with H partially substituted with small amounts of aromatic comonomers X, with the main scope of enhancing the polymerization rate, were apparently able to obtain products with improved randomness, especially when X was vanillic (i. e., 4-hydroxy-3-methoxybenzoic) acid.…”
Section: Introductionmentioning
confidence: 99%
“…We had the same approach to the compatibilization of blends of PE1"-16) or poly(ethy1ene terephthalate) 598 T. Miteva, L. Minkova (PET)17) and a semirigid LCP. It was found that the addition of small amounts of ad hoc synthesized PE-g-LCP or PET-LCP copolymers, gave rise to an improvement of the interfacial adhesionl6, 17) and to a significant improvement of the tensile ~t r e n g t h '~) and the elongation to breaki6.I7) of these blends.…”
Section: Introductionmentioning
confidence: 98%